Fluororesin film, metal-coated laminated board, and circuit board
By adopting specific compositions and surface treatment techniques, a fluororesin film is prepared, which has excellent contact angle characteristics and high uniform bonding strength in the center and at the left and right ends 100 mm away from each other, which solves the problem of uneven bonding of the existing fluororesin film and is suitable for high-frequency circuit substrates.
Patent Information
- Application Number
- CN202380054004.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-22
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-28
AI Technical Summary
The conventional fluororesin film has uneven adhesion in the high-frequency circuit substrate, which leads to a problem of circuit peeling when used in the high-frequency region.
The film made of a composition containing a fluororesin has the characteristics of a contact angle with water of 105° or less and a contact angle with n-hexadecane of 45° or less in the center and at a position 100 mm from the left and right ends, and improves the uniformity of the bonding strength by preferable surface treatment and composition.
The bonding strength uniformity of the fluororesin film is achieved, and stable bonding performance can be provided in the high-frequency circuit substrate, reducing the risk of circuit peeling.
Smart Images

Figure BDA0005243240110000211
Abstract
Description
Technical Field
[0001] The present disclosure relates to a fluororesin film, a metal-clad laminate, and a circuit board. Background Art
[0002] Epoxy resins and polyimide resins are widely used as insulating layers in circuit boards. In recent years, for high-frequency circuit boards used in applications in the high-frequency range of tens of gigahertz, some structures in which a fluororesin insulating layer is formed on a metal foil have been proposed from the perspective of dielectric properties and hygroscopicity.
[0003] In such a printed wiring board, adhesion to a metal foil can be obtained by subjecting the fluororesin film to a surface treatment.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2019-11413
[0007] Patent Document 2: Japanese Patent Application Laid-Open No. 2008-200991
[0008] Patent Document 3: International Publication No. 2020 / 066457 Summary of the invention
[0009] Problems to be solved by the invention
[0010] An object of the present disclosure is to provide a fluororesin film having high uniformity in the adhesive strength of the film.
[0011] Means for solving problems
[0012] The present disclosure relates to a fluororesin film, which is a film composed of a composition containing a fluororesin, wherein on at least one surface, at the center and at a position 100 mm away from each left and right end, the average value of the contact angle with water measured at 5 locations every 100 mm with respect to the traveling direction is 105° or less, and the average value of the contact angle with n-hexadecane measured at 5 locations every 100 mm with respect to the traveling direction is 45° or less.
[0013] The fluororesin film preferably has a film width of 400 mm or more.
[0014] The fluororesin preferably contains tetrafluoroethylene-perfluoroalkylvinyl ether (PFA) and / or tetrafluoroethylene-hexafluoropropylene (FEP).
[0015] The fluororesin film preferably has a dielectric loss tangent of less than 0.0015 at 10 GHz.
[0016] The fluororesin film is preferably 6The number of unstable functional groups in the main chain carbon atoms is less than 10.
[0017] The fluororesin film preferably has a bonding strength of 0.8 N / mm or more between the metal foil having a surface roughness Rz of 1.5 μm or less and the fluororesin film at the center and at a position 100 mm from each of the left and right ends.
[0018] The fluororesin film preferably has an adhesive strength of 0.8 N / mm or more between the prepreg comprising epoxy resin and / or polyphenylene ether and the fluororesin film at the center and at a position 100 mm from each of the left and right ends.
[0019] The bonding temperature of the fluororesin film and the metal foil is preferably 200° C. or higher. The fluororesin film is preferably used for a metal-clad laminate.
[0020] The present invention also relates to a metal-clad laminate comprising a metal foil and the above-mentioned fluororesin film as essential layers.
[0021] The present invention also relates to a metal-coated laminate, which is a laminate composed of a metal foil having a surface roughness Rz of less than 1.5 μm and a fluororesin film, characterized in that the contact angle with water at the center of the fluororesin film surface not facing the metal foil and at a position 100 mm away from the left and right ends is less than 105°, and the contact angle with n-hexadecane is less than 45°.
[0022] In the metal-clad laminate, the surface roughness Rz of the metal foil is preferably 1.5 μm or less.
[0023] The metal-clad laminate of the present disclosure preferably has a bonding strength of 0.8 N / mm or more between the prepreg and the laminate at the center and at a position 100 mm from each of the left and right ends.
[0024] The metal-coated laminate disclosed in the present invention also has layers other than metal foil and fluororesin film, and the layers other than metal foil and fluororesin film are preferably at least one selected from the group consisting of polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether and polybutadiene.
[0025] The present disclosure also relates to a circuit board, characterized by comprising the above-mentioned metal-clad laminate.
[0026] Effects of the Invention
[0027] The fluororesin film of the present disclosure has the effect of high uniformity of the adhesive strength of the film. DETAILED DESCRIPTION
[0028] Hereinafter, the present disclosure will be described in detail.
[0029] When a fluororesin film is used as a substrate for a metal-clad laminate, a metal foil or other resin may be laminated on the substrate. Fluororesin is a resin with low adhesiveness, and therefore, there is a demand for improving the adhesiveness in this case.
[0030] In order to improve such adhesiveness, it is known to subject the fluororesin film to surface treatment such as plasma treatment, corona treatment, sputtering treatment, etc. However, it is difficult to perform uniform surface treatment in such treatments, and uneven treatment often occurs.
[0031] However, when a fluororesin film is used in a printed wiring board, metal wiring is formed in a portion where the surface treatment is weak, which causes peeling after the circuit is formed. This causes concerns that the quality may not meet customer requirements, and uneven adhesion becomes a major problem. Therefore, in order to improve this, a fluororesin film having a uniform surface state is required.
[0032] In view of the above problems, the present disclosure relates to a fluororesin film having a uniform surface state, wherein the contact angle with water at the center and at a distance of 100 mm from the left and right ends is 105° or less, and the contact angle with n-hexadecane is 45° or less, in order to implement uniform surface treatment.
[0033] These aspects are described in detail below.
[0034] (Surface state of fluororesin film)
[0035] The fluororesin film of the present disclosure satisfies the following conditions: the contact angle with water is 105° or less at the center and at a position 100 mm from each of the left and right ends, and the contact angle with n-hexadecane is 45° or less.
[0036] If a surface treatment is performed to improve the adhesion of the fluororesin film, the contact angles of the film surface with water and n-hexadecane become smaller. However, depending on the state of the surface treatment, the contact angle of the surface may deviate, and there may be a portion where the contact angle is not sufficiently reduced. The present disclosure is characterized in that this point is improved by performing a surface treatment with high uniformity, and as the type of the surface treatment, a treatment method and treatment conditions that can fully reduce the surface tension for both water and an organic solvent are selected.
[0037] The surface treatment state of the film is particularly likely to differ between the end and the center of the film. Therefore, the present disclosure is characterized in that the above-mentioned contact angle is equally satisfied at both the end and the center.
[0038] Regarding the surface condition of the fluororesin film disclosed in the present invention, the arithmetic average of the contact angles with water measured at 5 locations every 100 mm with respect to the traveling direction at all three locations of the center and 100 mm from the left and right ends is 105° or less, and the arithmetic average of the contact angles with n-hexadecane measured at 5 locations every 100 mm with respect to the traveling direction is 45° or less.
[0039] The fluororesin film disclosed in the present invention may satisfy the above parameters on both sides or on only one side.
[0040] (Fluororesin film)
[0041] The fluororesin film disclosed in the present invention is preferably a long strip film. In the case of a long strip film, there are directions in the width direction and the length direction, and the length direction is the long direction. In addition, three locations, namely, the center portion relative to the width direction and the location 100 mm away from both ends, are used as measurement positions.
[0042] For each of these three measurement positions, an arbitrary location was set as a first measurement point, and the contact angle was measured at five locations every 100 mm in the longitudinal direction from the measurement point. The average of these measured values was used as the contact angle in the present disclosure.
[0043] The contact angles at five locations were measured at three locations in the width direction, respectively. However, in the length direction, the contact angles at five locations were measured at the same location and the average was taken.
[0044] Like this, when 5 places are measured with the contact angle of water and n-hexadecane, this contact angle is respectively below 105 °, below 45 °.By setting like this, above-mentioned problem can be solved.The details of the relation property of water and n-hexadecane with respect to bonding strength are still unclear, but infer that it is preferably certain scope from the following viewpoint.
[0045] The decrease in the contact angle with water suggests that there are more polar components (functional groups) that interact strongly with water on the film surface. In addition, the decrease in the contact angle with n-hexadecane suggests that there are more non-polar components that interact strongly with n-hexadecane on the surface. Adhesion requires high wettability to increase the contact area with the target material. In addition, the substrates need to be firmly bonded to each other through chemical bonds, anchoring effects, etc. Fluorine has low wettability to all materials, so it is speculated that increasing the interaction between polar and non-polar components to increase wettability is the main reason for improving bonding strength.
[0046] In the present disclosure, the contact angle refers to the static contact angle, which is measured using a fully automatic contact angle meter DropMaster700 (manufactured by Kyowa Interface Chemical Co., Ltd.) in the following manner. 2 μL of solution is dripped onto a horizontally placed substrate from a microsyringe, and a still image is taken 1 second after the dripping with a video microscope to obtain the static contact angle. The measured value of the static contact angle is measured at a specified location, and the average value is calculated and used.
[0047] The average value of the contact angle with water is more preferably 105° or less, more preferably 100° or less, and further preferably 90° or less. The average value of the contact angle with n-hexadecane is more preferably 45° or less, more preferably 40° or less, and further preferably 35° or less. The method for producing a fluororesin film having such a contact angle is described in detail below.
[0048] The thickness of the fluororesin film disclosed in the present invention is preferably 5 μm to 150 μm. From the perspective of having sufficient performance as a substrate film, it is preferably within this range. The lower limit of the thickness is more preferably 5 μm, and further preferably 10 μm. The upper limit of the thickness is more preferably 150 μm, and further preferably 100 μm.
[0049] In the present disclosure, the thickness of the film is measured at 12 locations every 5 mm in the width direction and every 200 mm in the traveling direction. Then, for the same width direction, the thickness of the 12 locations is arithmetic averaged in the traveling direction. These values become the average of the film thickness in the traveling direction measured every 5 mm in the width direction. Then, the arithmetic average of all values of the average of the film thickness in the traveling direction measured every 5 mm in the width direction is taken as the average of the film thickness of the entire surface.
[0050] When the thus obtained average film thickness is compared with the average film thickness in the running direction every 5 mm in the width direction, it is preferred that all the average film thickness in the running direction every 5 mm in the width direction be values within the range of ±2 μm from the average value.
[0051] This means that the film has a very high uniformity of thickness. If the film has such a high uniformity, when the long film is rolled up, the difference in thickness in this state is small, so the film with high uniformity can be rolled up in a good state. Therefore, it is preferred from the aspect of not easily causing the disadvantages caused by the subsequent lamination with the metal foil. Furthermore, the characteristic impedance can be made into a good range.
[0052] From the viewpoint of both the surface treatment state and the film thickness, a film with high uniformity is preferred because uniform bonding can be achieved, particularly in the application of bonding to a metal foil.
[0053] The fluororesin film disclosed in the present invention is preferably a long film. More specifically, the width is preferably 400 mm or more and the length is preferably 3 m or more. From the perspective of productivity, the width is more preferably 500 mm or more. In addition, the length is more preferably 10 m or more. Such a long film is preferably a roll film.
[0054] (Fluororesin)
[0055] The fluororesin constituting the fluororesin film of the present disclosure preferably has a small number of unstable functional groups. Such a fluororesin can be prepared by adjusting the conditions during the production (polymerization reaction), or by subjecting the polymerized fluororesin to a fluorine gas treatment (fluorination treatment), a heat treatment, a supercritical gas extraction treatment, etc. to reduce the number of unstable functional groups. In terms of excellent treatment efficiency, part or all of the unstable functional groups are converted into -CF 3 From the viewpoint of forming a stable terminal group, a fluorine gas treatment is preferred. If a fluororesin having a reduced number of unstable functional groups is used, it is preferred from the viewpoint of reducing the electrostatic tangent and reducing the loss of electric signals.
[0056] The fluororesin disclosed in the present invention is preferably 6 The number of unstable functional groups in the main chain carbon atoms is less than 350. By reducing the number of unstable functional groups, gas generation during melt molding can be suppressed, and uneven thickness caused by drift of the molten resin due to gas stagnating near the slit of the T-die can be suppressed.
[0057] The number of unstable functional groups is 1×10 6 The number of main chain carbon atoms is more preferably less than 250, further preferably less than 100, further preferably less than 20, and most preferably less than 10.
[0058] Specific examples of unstable functional groups include -COF, -COOH free (free COOH), -COOH bonded (associated -COOH), -CH 2 OH, -CONH 2 、-COOCH 3 etc. functional groups.
[0059] Specifically, the number of unstable functional groups is determined by the following method. First, a fluororesin is melted and compression molded to produce a film having a thickness of 0.25 mm to 0.3 mm. The film is analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum of the fluororesin and a differential spectrum from a background spectrum of a completely fluorinated film without functional groups. The number of unstable functional groups per 1×10 6 The number of unstable functional groups in the main chain carbon atoms.
[0060] N=I×K / t (A)
[0061] I: Absorbance
[0062] K: Correction coefficient
[0063] t: film thickness (mm)
[0064] For reference, regarding the unstable functional groups in this specification, the absorption frequency, molar absorption coefficient and correction coefficient are shown in Table 1. In addition, the molar absorption coefficient is determined from the FT-IR measurement data of the low molecular model compound.
[0065] [Table 1]
[0066] Unstable functional groups Absorption frequency (cm-1) Molar absorption coefficient (1 / cm / mol) Correction factor Model compounds -COF 1883 600 388 <![CDATA[C 7 F 15 COF]]> -COOH(free) 1815 530 439 <![CDATA[H(CF 2 ) 6 COOH]]> -COOH(bonding) 1779 530 439 <![CDATA[H(CF 2 ) 6 COOH]]> <![CDATA[-COOCH 3 ]]> 1795 680 342 <![CDATA[C 7 F 15 COOCH 3 ]]> <![CDATA[-CONH 2 ]]> 3436 506 460 <![CDATA[C 7 F 15 CONH 2 ]]> <![CDATA[-CH 2 OH]]> 3648 104 2236 <![CDATA[C 7 F 15 CH 2 OH]]> <![CDATA[-CF 2 H]]> 3020 8.8 26485 <![CDATA[H(CF 2 CF 2 ) 3 CH 2 OH]]> -OC(=O)OR 1817 - 1426 -
[0067] The fluorination treatment can be performed by bringing the fluorine-containing compound into contact with the fluorine-containing resin which has not been fluorinated.
[0068] The fluorine-containing compound is not particularly limited, and examples thereof include a fluorine radical source that generates fluorine radicals under fluorination treatment conditions. Examples of the fluorine radical source include F 2 Gas, CoF 3 , AgF 2 、UF 6 、OF 2 、N 2 F 2 CF 3 OF, fluorinated halogens (such as IF 5 , ClF 3 )wait.
[0069] The above F 2 The fluorine radical source such as gas can be a fluorine radical source with a concentration of 100%, but is preferably mixed with an inert gas and diluted to 5% to 50% by mass for use, and more preferably diluted to 15% to 30% by mass for use. As the above-mentioned inert gas, nitrogen, helium, argon, etc. can be cited, and nitrogen is preferred from an economical aspect.
[0070] The conditions of the fluorination treatment are not particularly limited. The fluorinated resin in a molten state may be brought into contact with the fluorine-containing compound. However, the treatment may be carried out at a temperature below the melting point of the fluorinated resin, preferably at 20°C to 220°C, and more preferably at 100°C to 200°C. The fluorination treatment is usually carried out for 1 to 30 hours, preferably 5 to 25 hours. The fluorination treatment is preferably carried out by contacting the fluorinated resin with fluorine gas (F 2 Gas) contact treatment.
[0071] In the present specification, the content of each monomer unit constituting the fluororesin can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and fluorescent X-ray analysis according to the types of monomers.
[0072] The resin constituting the fluororesin film of the present disclosure is not particularly limited, as long as it is a polymer containing fluorine atoms in part. Fluororesins are more preferably fluororesins that can be melt-molded, and examples thereof include tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers (PFA), copolymers having chlorotrifluoroethylene (CTFE) units (CTFE copolymers), tetrafluoroethylene-hexafluoropropylene copolymers (FEP), tetrafluoroethylene-ethylene copolymers (ETFE), polychlorotrifluoroethylene (PCTFE), chlorotrifluoroethylene-ethylene copolymers (ECTFE), polyvinylidene fluoride (PVDF) and polyvinyl fluoride (PVF), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers (THV), tetrafluoroethylene-vinylidene fluoride copolymers, etc.
[0073] Among these melt-moldable fluororesins, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers (PFA) and tetrafluoroethylene-hexafluoropropylene copolymers (FEP) are preferred.
[0074] By using the above-mentioned melt-moldable fluororesin, melt molding is possible, so the processing cost can be suppressed compared with the case of using PTFE. Furthermore, the adhesion when bonding with metal foil can be improved.
[0075] The melting point of PFA is preferably 180 to 340° C., more preferably 230 to 330° C., and further preferably 280 to 320° C. The melting point is a temperature corresponding to a maximum value in a heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].
[0076] As the above-mentioned PFA, there is no particular limitation, and a copolymer in which the molar ratio of TFE units to PAVE units (TFE units / PAVE units) is 70 / 30 or more and less than 99.5 / 0.5 is preferred. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and a further preferred molar ratio is 80 / 20 or more and 98.5 / 1.5 or less. If the TFE unit is too few, the mechanical properties tend to decrease; if it is too much, the melting point is too high and the moldability tends to decrease. The above-mentioned PFA can be a copolymer consisting only of TFE and PAVE, and is also preferably a copolymer in which the monomer units from monomers copolymerizable with TFE and PAVE are 0.1 mol% to 10 mol%, and the total of TFE units and PAVE units is 90 mol% to 99.9 mol%. As monomers copolymerizable with TFE and PAVE, HFP, CZ 3 Z 4 =CZ 5 (CF2 ) n Z 6 (Where Z 3 , Z 4 and Z 5 are the same or different, representing a hydrogen atom or a fluorine atom, Z 6 represents a hydrogen atom, a fluorine atom or a chlorine atom, and n represents an integer from 2 to 10), and CF 2 =CF-OCH 2 -Rf 7 (Where Rf 7 The alkyl perfluorovinyl ether derivative represented by (represents a perfluoroalkyl group having 1 to 5 carbon atoms) is used as another copolymerizable monomer, for example, a cyclic hydrocarbon monomer having an acid anhydride group, and examples of the acid anhydride monomer include itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, and maleic anhydride. The acid anhydride monomer may be used alone or in combination of two or more.
[0077] The melt flow rate (MFR) of the above-mentioned PFA is preferably 0.1 g / 10 min to 100 g / 10 min, more preferably 0.5 g / 10 min to 90 g / 10 min, and further preferably 1.0 g / 10 min to 85 g / 10 min. It should be noted that in this specification, MFR is a value measured under the conditions of a temperature of 372° C. and a load of 5.0 kg according to ASTM D3307.
[0078] As the above-mentioned FEP, there is no particular limitation, but a copolymer in which the molar ratio of TFE units to HFP units (TFE units / HFP units) is 70 / 30 or more and less than 99 / 1 is preferred. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and a further preferred molar ratio is 80 / 20 or more and 97 / 3 or less. If the TFE unit is too little, the mechanical properties tend to decrease; if it is too much, the melting point is too high and the moldability tends to decrease. FEP is also preferably a copolymer in which the monomer units from monomers copolymerizable with TFE and HFP are 0.1 mol% to 10 mol%, and the total of TFE units and HFP units is 90 mol% to 99.9 mol%. As monomers copolymerizable with TFE and HFP, alkyl perfluorovinyl ether derivatives can be cited.
[0079] The melting point of the FEP is preferably 150 to 320° C., more preferably 200 to 300° C., and even more preferably 240 to 280° C. The melting point is a temperature corresponding to a maximum value in a heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].
[0080] The MFR of the FEP is preferably 0.01 to 100 g / 10 min, more preferably 0.1 to 80 g / 10 min, further preferably 1 to 60 g / 10 min, particularly preferably 1 to 50 g / 10 min.
[0081] The fluororesin film disclosed herein may also contain components other than fluororesin. The components that may be contained are not particularly limited, and examples thereof include fillers such as silica particles and glass short fibers, and fluorine-free thermosetting resins / thermoplastic resins. The content of components other than fluororesin is preferably 5% by mass or less (more preferably 3% or less, 1% or less, etc.).
[0082] The fluororesin-containing composition of the present disclosure may contain spherical silica particles, which improves the fluidity of the resin and facilitates molding even when a large amount of silica is blended.
[0083] The above-mentioned spherical silica particles refer to particles whose shape is close to a true sphere. Specifically, the sphericity is preferably above 0.80, more preferably above 0.85, further preferably above 0.90, and most preferably above 0.95. The sphericity is calculated as follows: a photograph is taken using an SEM, and the area and perimeter of the observed particles are calculated as a value calculated by (sphericity) = {4π×(area) ÷ (perimeter) 2}. The closer to 1, the closer to a true sphere. Specifically, the arithmetic mean value of 100 particles measured using an image processing device (Spectris Co., Ltd.: FPIA-3000) is used.
[0084] For the above-mentioned spherical silica particles, when the volume is integrated from the side with a smaller particle size, preferably D90 / D10 is 2 or more (preferably 2.3 or more, 2.5 or more), and D50 is 10 μm or less. Furthermore, D90 / D50 is preferably 1.5 or more (more preferably 1.6 or more). D50 / D10 is preferably 1.5 or more (more preferably 1.6 or more). Since spherical silica particles with a small particle size may enter the gaps between spherical silica particles with a large particle size, the filling property is excellent and the fluidity can be improved. In particular, as a particle size distribution, it is preferred that the frequency of the side with a smaller particle size is larger than that of a Gaussian curve. The particle size can be measured using a laser diffraction scattering particle size distribution measuring device. In addition, it is preferred to remove coarse particles with a particle size larger than a specified particle size using a filter or the like.
[0085] The water absorption of the spherical silica particles is preferably 1.0% or less, and more preferably 0.5% or less. The water absorption is based on the mass of the silica particles when dried. In the measurement of water absorption, the sample in a dry state is placed at 40°C 80% RH for 1 hour, and the water generated by heating at 200°C is measured using a Karl Fischer moisture meter, and the water absorption is calculated.
[0086] Alternatively, the spherical silica particles may be prepared by heating the fluororesin composition at 600° C. for 30 minutes in an air atmosphere to burn off the fluororesin, taking out the spherical silica particles, and then measuring the above parameters by the above methods.
[0087] The silica powder of the present invention may be surface treated. By previously performing the surface treatment, aggregation of the silica particles can be suppressed, and the silica particles can be well dispersed in the resin composition.
[0088] The surface treatment is not particularly limited, and any known surface treatment can be used. Specifically, for example, treatment with silane coupling agents such as epoxy silane, amino silane, vinyl silane, acrylic silane, hydrophobic alkyl silane, phenyl silane, and fluoroalkyl silane having a reactive functional group, plasma treatment, fluorination treatment, etc. can be cited.
[0089] Examples of the silane coupling agent include epoxysilanes such as γ-glycidoxypropyltriethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, aminosilanes such as aminopropyltriethoxysilane and N-phenylaminopropyltrimethoxysilane, vinylsilanes such as vinyltrimethoxysilane, and acrylsilanes such as acryloxytrimethoxysilane.
[0090] The spherical silica can use commercially available silica particles that satisfy the above properties. As commercially available silica particles, for example, Denka fused silica FB grade (manufactured by Denka Co., Ltd.), Denka fused silica SFP grade (manufactured by Denka Co., Ltd.), EXCELICA (manufactured by Tokuyama Co., Ltd.), high-purity synthetic spherical silica ADMAFINE (manufactured by Admatechs Co., Ltd.), ADMANANO (manufactured by Admatechs Co., Ltd.), ADMAFUSE (manufactured by Admatechs Co., Ltd.), etc. can be cited.
[0091] When the spherical silica is compounded, the compounding amount is preferably 5% by mass or less (more preferably 3% or less, 1% or less, etc.) based on the mass of the fluororesin long film.
[0092] (Surface oxygen ratio)
[0093] The film disclosed herein preferably has an oxygen element ratio of 1.35 atomic % or more when the surface state of one or both surfaces is measured by ESCA after heat treatment at 180° C. for 3 minutes. The oxygen atomic ratio is more preferably 1.5 atomic % or more, further preferably 1.8 atomic % or more, and most preferably 2.0 atomic % or more.
[0094] In order to make the surface of the fluororesin film of the present disclosure have a predetermined contact angle, it is preferred that the oxygen element ratio be increased by performing a surface treatment such as plasma treatment. Thus, the fluororesin film of the present disclosure can be obtained by performing a surface treatment on a film obtained by extrusion molding or a film obtained by applying a liquid composition containing a fluororesin powder to a substrate and drying it, thereby increasing the oxygen element ratio and improving adhesion, so that the oxygen element ratio on the surface is within the above range.
[0095] The film disclosed herein may be a fluorine film having a difference of 1.0 atomic % or more between the oxygen element ratio when the surface state is measured by a scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA) and the oxygen element ratio when the film is etched in the depth direction by an argon cluster ion beam at an incident angle of 45° for 15 minutes and measured by a scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA). By increasing only the oxygen element ratio on the surface that contributes to bonding, sufficient bonding strength can be obtained without impairing dielectric properties.
[0096] The heat treatment at 180° C. for 3 minutes is performed by placing the film on a metal tray and performing the treatment in an electric furnace under an air atmosphere.
[0097] The fluororesin film disclosed in the present invention preferably has an absolute value of the dimensional change rate in MD and TD before and after the heat treatment of 2.0% or less when it is cooled to 25°C after heat treatment for 10 minutes. The above-mentioned dimensional change rate is more preferably 1.8% or less, and most preferably 1.5% or less. In the present disclosure, regarding the dimensional change rate, a film sample cut into 300 mm squares is marked with 180 mm intervals, and a heat treatment is performed for 10 minutes in an electric furnace set at 180°C in an air atmosphere without applying a load, and then cooled to 25°C, and the mark intervals in the MD direction and TD direction of the cooled film are measured, and calculated from the change in the mark intervals before and after the heat treatment.
[0098] In order to obtain a fluororesin film having such a dimensional change rate, it is preferable to perform an annealing treatment as described in detail below.
[0099] The resin film disclosed herein preferably has a dielectric loss tangent of less than 0.0015 at 10 GHz. By being within this range, the loss of electrical signals in the circuit can be suppressed to a low level, which is preferred from this point of view. The above dielectric loss tangent is more preferably less than 0.0013, and further preferably less than 0.0010. In order to make the dielectric loss tangent within the above range, it is preferred to use a resin with few unstable functional groups, and it is more preferred to use a fluororesin that has been subjected to terminal fluorination treatment.
[0100] When the above-mentioned fluororesin film is bonded to a metal foil having a surface roughness Rz of 1.5 μm or less using a vacuum hot press under the conditions of a temperature above the melting point of the fluororesin and below the melting point + 30°C, a pressure of 1.5 MPa to 3.0 MPa, and a time of 300 seconds to 600 seconds, the bonding strength to the center of the fluororesin film and the portion 100 mm away from the left and right ends is preferably 0.8 N / mm or more.
[0101] That is, the film has sufficient adhesive strength at both the center and the end portions, and the uniformity of the adhesiveness is high.
[0102] In addition, the adhesive strength in this specification refers to the arithmetic mean of the measured values measured at 5 points every 100 mm with respect to the traveling direction, similarly to the measurement of the contact angle.
[0103] The fluororesin film preferably has a bonding strength of 0.8 N / mm or more at the center and 100 mm from the left and right ends of the fluororesin film as a prepreg of a thermosetting resin. It should be noted that the bonding strength here refers to the bonding strength when bonding by the method described in the examples.
[0104] In addition, this adhesive strength also means the average value of the measured values measured at 5 points every 100 mm with respect to the running direction, similarly to the measurement of the contact angle.
[0105] The fluororesin film preferably has an adhesive strength of more than 30 N / m when the films are bonded to each other on the same surface at 200° C. for only one side or both sides. With such an adhesive strength, even after the fluororesin film is heat-treated, the film has excellent adhesion when used in combination with various other substrates. The adhesive strength is more preferably more than 50 N / m, and even more preferably more than 100 N / m.
[0106] (Method for producing fluororesin film of the present disclosure)
[0107] The fluororesin film of the present disclosure is generally produced by extrusion melt molding in which a molten resin is extruded from a T-die to be molded into a film shape, and after cooling, the film is wound up.
[0108] The fluororesin film disclosed in the present invention is mainly characterized by the method of surface treatment. However, when the resin film itself subjected to the surface treatment is also a film with high uniformity, it is preferred that the uniformity of the film as a whole is high. Therefore, a method for manufacturing a fluororesin film with less uneven thickness is particularly preferred.
[0109] From this aspect, in extrusion melt molding, the air gap distance from the end of the T-die where the resin flows out to the initial contact with the roller, the MFR of the resin used, the melting temperature and pressure during film production, the slit width of the T-die, the gap width, etc., particularly affect the thickness of the resin film. Therefore, by appropriately adjusting these, a smooth resin film that satisfies the above parameters can be obtained.
[0110] Furthermore, it is also preferable to adjust the MFR. That is, by shortening the air gap and reducing the presence of the air layer between the melt and the first roll, the unevenness of the film thickness is reduced.
[0111] The specific method of the above-mentioned surface modification is not particularly limited and can be carried out by any known method. The surface modification of the fluororesin film can be carried out by a discharge treatment based on corona discharge treatment or glow discharge treatment, plasma discharge treatment, sputtering treatment, etc. that has been carried out in the past. For example, in addition to being able to control the surface free energy by introducing oxygen, nitrogen, hydrogen, etc. into the discharge atmosphere, the surface to be modified is exposed to an atmosphere of an inert gas containing an organic compound as an inert gas containing an organic compound, and a high-frequency voltage is applied between the electrodes to generate a discharge, thereby generating active species on the surface, and then introducing the functional groups of the organic compound or the graft-polymerized organic compound, thereby surface modification can be carried out. As the above-mentioned inert gas, for example, nitrogen, helium, argon, etc. can be cited.
[0112] Examples of the organic compound in the above-mentioned inert gas containing organic compounds include polymerizable or non-polymerizable organic compounds containing oxygen atoms, such as vinyl esters such as vinyl acetate and vinyl formate; acrylic esters such as glycidyl methacrylate; ethers such as vinyl ethyl ether, vinyl methyl ether, and glycidyl methyl ether; carboxylic acids such as acetic acid and formic acid; alcohols such as methanol, ethanol, phenol, and ethylene glycol; ketones such as acetone and methyl ethyl ketone; carboxylic acid esters such as ethyl acetate and ethyl formate; acrylic acids such as acrylic acid and methacrylic acid, etc. Among these, vinyl esters, acrylic esters, and ketones are preferred, and vinyl acetate and glycidyl methacrylate are particularly preferred, from the perspective of the surface being less likely to be deactivated after modification, that is, having a long life, and being easy to handle.
[0113] The concentration of the organic compound in the above-mentioned inert gas containing organic compounds varies depending on the type of organic compound, the type of fluororesin to be surface-modified, etc., and is usually 0.1 volume % to 3.0 volume %, preferably 0.1 volume % to 1.0 volume %. The discharge conditions can be appropriately selected according to the degree of surface modification as the target, the type of fluororesin, the type or concentration of the organic compound, etc. Usually, when the discharge amount is 50W·min / m 2 ~1500W·min / m 2 , preferably 70W·min / m 2 Above 1400W·min / m 2 The discharge treatment is performed within the following range. The treatment temperature may be any temperature within the range of 0°C to 100°C. Due to concerns about elongation, wrinkles, etc. of the film, it is preferably 80°C or less.
[0114] In the above surface modification, it is preferred that the discharge degree representing the output per unit area be 1.0 to 10 (W / cm 2 ) and the gas concentration / linear velocity ratio was adjusted to be in the range of 0.005 to 0.05 (L / m).
[0115] The gas concentration / linear velocity ratio mentioned here represents the ratio obtained by dividing the concentration of the organic compound in the inert gas containing the organic compound by the linear velocity. If it is less than 0.005 (L / m), the space is not filled with sufficient gas relative to the conveying speed, and the activated gas is difficult to contact the film surface, and the uniformity in the surface is reduced. If it is higher than 0.05 (L / m), the surface is over-processed and damaged, so low molecular weight compounds are generated on the surface, thereby forming a fragile layer, which leads to a reduction in bonding strength. Thus, it is inferred that the film surface is more evenly processed and a specified adhesion is obtained, so the processing within this range is particularly preferred.
[0116] Regarding the degree of surface modification, if the surface adhesion is reduced due to heat during post-processing, the oxygen content is 2.0% or more, preferably 2.5% or more, more preferably 3.0% or more, and more preferably 3.5% or more when observed by ESCA. There is no particular upper limit, but in view of the impact on productivity and other physical properties, it is preferably 25.0% or less. There is no particular limit on the nitrogen content, but it is preferably 0.1% or more. In addition, the thickness of a fluororesin film is preferably 2.5μm to 1000μm, more preferably 5μm to 500μm, and more preferably 7μm to 150μm.
[0117] Such treatment may be performed on only one side of the film or on both sides.
[0118] (Annealing treatment)
[0119] The fluororesin film of the present disclosure may be subjected to annealing treatment after the above-mentioned surface treatment. As described above, the fluororesin film of the present disclosure preferably has dimensional stability when laminated with a metal foil. Therefore, it is preferred that the shrinkage rate when heated is low.
[0120] Fluororesin films obtained by extrusion melt molding often experience thermal shrinkage due to residual internal stress, and such thermal shrinkage can adversely affect dimensional stability when laminated with metal foil. Therefore, it is preferred to relax the internal stress by annealing. Annealing can be performed by heat treatment. The heat treatment can be performed, for example, by passing through a heating furnace in a roll-to-roll manner.
[0121] In the manufacture of the fluororesin film disclosed herein, it is preferred to perform annealing after the above-mentioned corona discharge treatment. In addition, sometimes heat treatment is performed in the process of laminating the film with other materials such as metal foil. Therefore, by undergoing these heat treatments, the amount of oxygen on the surface of the fluororesin film is reduced. Thus, it is preferred to perform surface modification under the condition of obtaining sufficient surface oxygen amount when the fluororesin film is actually laminated with other materials such as metal foil.
[0122] The annealing temperature is preferably higher than the glass transition temperature - 20°C and lower than the melting point, more preferably higher than the glass transition temperature and lower than the melting point - 20°C, and further preferably higher than the glass transition temperature and lower than the melting point - 60°C. The annealing time is not particularly limited and may be appropriately adjusted within a range of, for example, 0.5 to 60 minutes.
[0123] When heating in the roll-to-roll manner, the tension can be appropriately adjusted according to the film thickness, set temperature, etc., and is preferably 20 N / m or less. By heating under such conditions, internal stress can be fully relaxed and dimensional changes will not occur, which is preferred.
[0124] The order of the surface treatment and the annealing treatment is not particularly limited, and the number of times each step is performed is not limited to once, but may be performed twice or more.
[0125] The present disclosure also relates to a laminate, characterized in that a metal foil is bonded to one or both sides of the above-mentioned fluororesin film. As described above, the film containing fluororesin of the present disclosure has excellent adhesion. The Rz of the above-mentioned metal foil is preferably 1.5 μm or less. That is, the fluororesin composition of the present disclosure also has excellent adhesion to a metal foil with high smoothness and Rz of 1.5 μm or less. Furthermore, the metal foil only needs to have a surface with at least 1.5 μm or less bonded to the above-mentioned fluororesin film, and the Rz value of the other surface is not particularly limited.
[0126] The thickness of the metal foil is not particularly limited, but is preferably in the range of 1 μm to 100 μm, more preferably in the range of 5 μm to 50 μm, and even more preferably in the range of 9 μm to 35 μm.
[0127] The metal foil is not particularly limited, but copper foil is particularly preferred. The copper foil is not particularly limited, and specific examples thereof include rolled copper foil and electrolytic copper foil.
[0128] The copper foil having an Rz of 1.5 μm or less is not particularly limited, and commercially available copper foil can be used. Examples of commercially available copper foil having an Rz of 1.5 μm or less include electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil Co., Ltd.).
[0129] The metal foil may be subjected to a surface treatment in order to improve the bonding strength with the fluororesin film of the present disclosure.
[0130] The surface treatment is not particularly limited, and is silane coupling treatment, plasma treatment, corona treatment, UV treatment, electron beam treatment, etc. The reactive functional group of the silane coupling agent is not particularly limited. From the aspect of adhesion to the resin substrate, it is preferred to have at least one selected from amino, (meth) acryloyl, mercapto and epoxy groups at the terminal. In addition, the hydrolyzable group is not particularly limited, and alkoxy groups such as methoxy and ethoxy can be cited. The metal foil used in the present disclosure can be formed with a rust-proof layer (oxide film such as chromate, etc.), a heat-resistant layer, etc.
[0131] The surface-treated metal foil having the surface-treated layer formed of the above-mentioned silane compound on the surface of the metal foil can be produced by preparing a solution containing the silane compound and then surface-treating the metal foil with the solution.
[0132] The metal foil may have a roughening treatment layer on its surface in order to improve adhesion to the resin substrate.
[0133] It should be noted that, if the roughening treatment may reduce the performance required by the present disclosure, the roughening particles electrodeposited on the surface of the metal foil may be reduced as needed, or the roughening treatment may not be performed.
[0134] From the perspective of improving various properties, one or more layers selected from the group consisting of a heat-resistant treatment layer, a rust-proof treatment layer, and a chromate treatment layer may be provided between the metal foil and the surface treatment layer. These layers may be a single layer or multiple layers.
[0135] In the above-mentioned laminate, the bonding strength between the metal foil and the fluororesin film is preferably 0.8N / mm or more. By applying the above-mentioned method, such bonding strength can be achieved. By making the bonding strength 0.9N / mm or more, and further 1.0N / mm or more, it can be suitable for use as a metal-coated laminate and a circuit substrate. It should be noted that the bonding strength herein refers to the bonding strength measured under the conditions described in the embodiments. In addition, in the case of a laminate in which the metal foil is bonded to the surface-treated surface of the fluororesin film that has been surface-treated on only one side, in order to improve the adhesion between the laminate and other materials, the surface of the fluororesin film that has not been surface-treated can also be subjected to surface modification.
[0136] The method for producing the laminated body includes a method of laminating a metal foil on the surface of a film, a vapor deposition method, a plating method, etc. As the method of laminating the metal foil, a method using hot pressing and a method using roll-to-roll lamination are mentioned.
[0137] When lamination is performed by hot pressing, the temperature may be -150° C. the melting point of the dielectric film to +40° C. The hot pressing time may be, for example, 1 minute to 30 minutes. The hot pressing pressure may be 0.1 MPa to 10 MPa.
[0138] When laminating by roll-to-roll lamination, the temperature may be the dielectric film melting point -150° C. to the dielectric film melting point +40° C. The speed is preferably 0.5 m / min or more, and more preferably 1.0 m / min or more from the viewpoint of productivity.
[0139] The pressure is preferably in the range of 10 kg / cm to 200 kg / cm, and more preferably 20 kg / cm or more to obtain good adhesion. The roll-to-roll laminating device is not particularly limited, but preferably has a pair or more of metal nip rollers, or a nip roller with a rubber roller on one side.
[0140] The above-mentioned laminate is preferably a long laminate. More specifically, it is preferably 400 mm or more in width and 3 m or more in length. From the perspective of productivity, the width is more preferably 500 mm or more. In addition, the length is more preferably 10 m or more. Such a long laminate is preferably a rolled laminate.
[0141] The metal-clad laminate of the present disclosure may further include a layer other than the metal foil and the fluororesin film.
[0142] The layer other than the metal foil and the fluororesin film is preferably at least one selected from the group consisting of polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether and polybutadiene.
[0143] The layers other than the metal foil and the fluororesin film are not particularly limited as long as they are composed of the above-mentioned resin. The thickness of the layers other than the metal foil and the fluororesin film is preferably within a range of 12 μm to 200 μm.
[0144] The metal-coated laminate of the present disclosure forms a metal layer on the surface layer of the film of the present invention. The metal layer may be formed on one side of the film or on both sides. As a method for forming the metal layer, a method of laminating a metal foil on the surface of the film, a vapor deposition method, a plating method, etc. may be cited. As a method for laminating a metal foil, a method using hot pressing and a method using roll-to-roll lamination may be cited.
[0145] The method of forming a composite of the metal foil, the base material layer and the fluororesin film is not particularly limited, and examples thereof include the following two methods.
[0146] (i) A method of laminating a metal foil, a substrate layer, and a preformed fluororesin film by a roll-to-roll process or by applying pressure under heating using a press. The layer facing the metal foil may be the substrate layer or the fluororesin layer.
[0147] (ii) A method of producing a laminate in which a fluororesin film is bonded to one surface of a metal foil, and laminating the fluororesin surface not facing the metal foil and the base material layer under heating and pressure.
[0148] The use of the metal-coated laminate disclosed in the present invention is not particularly limited, and it is used as a circuit substrate. A printed substrate refers to a plate-like component that is configured and fixed in a limited space while electrically connecting electronic components such as semiconductors and capacitor chips. There are no particular restrictions on the composition of the printed substrate formed by the present metal-coated laminate. The printed substrate can be any of a rigid substrate, a flexible substrate, and a rigid-flexible substrate. The printed substrate can be any of a single-sided substrate, a double-sided substrate, and a multi-layer substrate (build-up substrate, etc.). It is particularly suitable for use in flexible substrates and rigid substrates.
[0149] The circuit board is not particularly limited, and can be produced by a general method using the above-mentioned metal-clad laminate.
[0150] The laminate for the circuit board may also be a laminate having a metal foil layer, the above-mentioned fluororesin film and a substrate layer. The substrate layer is not particularly limited, but preferably has a cloth layer made of glass fiber and a resin film layer.
[0151] The above-mentioned cloth layer composed of glass fibers is a layer composed of glass cloth, glass nonwoven fabric, etc. As the glass cloth, commercially available glass cloth can be used. In order to improve the affinity with the fluororesin, it is preferably treated with a silane coupling agent. As the material of the glass cloth, E glass, C glass, A glass, S glass, D glass, NE glass, low dielectric constant glass, etc. can be cited. From the perspective of easy availability, E glass, S glass, and NE glass are preferred. As for the weaving method of the fiber, it can be plain or twill. The thickness of the glass cloth is usually 5μm to 90μm, preferably 10μm to 75μm, and it is preferred to use a glass cloth thinner than the fluororesin film used.
[0152] The laminate can use glass nonwoven fabric as the cloth layer composed of glass fiber. Glass nonwoven fabric is a material formed by bonding short glass fibers with a small amount of binder compound (resin or inorganic substance), or a material that maintains its shape by winding glass short fibers without using a binder compound, and commercial products can be used. The diameter of the glass short fibers is preferably 0.5 μm to 30 μm, and the fiber length is preferably 5 mm to 30 mm. As specific examples of binder compounds, resins such as epoxy resins, acrylic resins, cellulose, polyvinyl alcohol, and fluororesins, or inorganic substances such as silica compounds can be cited. The amount of binder compound used is usually 3% to 15% by mass relative to the glass short fibers. As the material of the glass short fibers, E glass, C glass, A glass, S glass, D glass, NE glass, low dielectric constant glass, etc. can be cited. The thickness of the glass nonwoven fabric is usually 50 μm to 1000 μm, preferably 100 μm to 900 μm. It should be noted that the thickness of the glass nonwoven fabric in the present application refers to the value measured using a digital gauge DG-925 (load 110 g, surface diameter 10 mm) manufactured by Ono Sakuki Co., Ltd. in accordance with JIS P8118: 1998. The glass nonwoven fabric may be treated with a silane coupling agent to improve affinity with fluororesin.
[0153] Since the porosity of most glass nonwoven fabrics is 80% or more, which is very high, it is preferable to use a glass nonwoven fabric thicker than the sheet made of fluororesin and compress it by pressure.
[0154] The cloth layer composed of the glass fiber may be a layer formed by laminating glass cloth and glass nonwoven fabric. In this way, the properties of each other are combined to obtain appropriate properties.
[0155] The cloth layer composed of the glass fiber may be in the state of a prepreg impregnated with a resin.
[0156] In the above-mentioned laminate, the cloth layer composed of glass fibers and the fluororesin film may be bonded at the interface, or the fluororesin film may be partially or entirely impregnated into the cloth layer composed of glass fibers.
[0157] In addition, a fluororesin composition may be impregnated into a cloth made of glass fiber to prepare a prepreg. The prepreg thus obtained may be further laminated with the fluororesin film disclosed herein. In this case, the fluororesin composition used in preparing the prepreg is not particularly limited, and the fluororesin film disclosed herein may also be used.
[0158] As the resin film used as the above-mentioned substrate, a heat-resistant resin film and a thermosetting resin film are preferred. As the heat-resistant resin film, polyimide, liquid crystal polymer, polyphenylene sulfide, etc. can be cited. As the thermosetting resin, thermosetting resins including epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether, polybutadiene, etc. can be cited.
[0159] The heat-resistant resin film and the thermosetting resin film may contain reinforcing fibers. The reinforcing fibers are not particularly limited, but are preferably glass cloth, and particularly low dielectric constant reinforcing fibers.
[0160] The dielectric properties, linear expansion coefficient, water absorption rate and other properties of the heat-resistant resin film and the thermosetting resin film are not particularly limited. For example, the dielectric constant at 20 GHz is preferably 3.8 or less, more preferably 3.4 or less, and further preferably 3.0 or less. The dielectric loss tangent at 20 GHz is preferably 0.0030 or less, more preferably 0.0025 or less, and further preferably 0.0020 or less. The linear expansion coefficient is preferably 100 ppm / °C or less, more preferably 70 ppm / °C or less, and further preferably 40 ppm / °C or less. The water absorption rate is preferably 1.0% or less, more preferably 0.5% or less, and further preferably 0.1% or less.
[0161] Example
[0162] The present disclosure is specifically described below based on examples. In the following examples, the ratio is expressed as a molar ratio.
[0163] (Example 1)
[0164] PFA (TFE / PPVE copolymer, composition: TFE / PPVE=98.2 / 1.8, MFR: 15.8g / 10min, melting point 305°C, glass transition temperature 92°C) as a fluororesin was put into an extruder at 360°C, extruded from a 1700mm wide T-die and pulled to a metal cooling roller, and then wound on a winding core to form a 1300mm wide, 50μm thick roll film. Both sides of the roll film were surface treated (while flowing near the discharge electrode of the corona discharge device and the roll-shaped ground electrode in a manner where the ratio of the gas concentration of vinyl acetate in nitrogen to the linear velocity was 0.014 (L / m), the film was continuously passed along the roll-shaped ground electrode at a discharge rate of 1.4W / cm 2Both sides of the film were subjected to corona discharge treatment, and the surface-treated long film was rolled up to obtain a surface-treated sample. Evaluation was then performed.
[0165] (Example 2)
[0166] The discharge degree is 2.3W / cm 2 , a surface-treated sample was obtained in the same manner as in Example 1 except for the above, and then evaluated.
[0167] (Example 3)
[0168] The discharge degree is 2.9W / cm 2 , a surface-treated sample was obtained in the same manner as in Example 1 except for the above, and then evaluated.
[0169] (Example 4)
[0170] The discharge degree is 3.7W / cm 2 , a surface-treated sample was obtained in the same manner as in Example 1 except for the above, and then evaluated.
[0171] (Example 5)
[0172] A surface-treated sample was obtained in the same manner as in Example 3 except that the gas concentration / linear velocity ratio was changed to 0.007 L / m, and then evaluated.
[0173] (Example 6)
[0174] After obtaining a surface-treated sample in the same manner as in Example 3 except that a film obtained by a T-die method and having a width of 1300 mm and a thickness of 50 μm was cut into a film having a width of 500 mm, evaluation was performed.
[0175] (Example 7)
[0176] A surface-treated sample was obtained in the same manner as in Example 3 except that the fluororesin was PFA (TFE / PPVE copolymer, composition: TFE / PPVE=97.7 / 2.3, MFR: 15.0 g / 10 min, melting point 300.9° C., glass transition temperature 93° C.), and the sample was evaluated.
[0177] (Comparative Example 1)
[0178] A surface-treated sample was obtained in the same manner as in Example 3 except that the gas concentration / linear velocity ratio was changed to 0.004 L / m, and then evaluated.
[0179] (Comparative Example 2)
[0180] Make the discharge degree 0.6W / cm 2, a surface-treated sample was obtained in the same manner as in Example 3 except for the above, and then evaluated.
[0181] (Comparative Example 3)
[0182] Evaluation was performed using samples without surface treatment.
[0183] (Static contact angle of water)
[0184] The static contact angle of water was measured using a fully automatic contact angle meter DropMaster700 (manufactured by Kyowa Interface Chemical Co., Ltd.) in the following manner. 2 μL of water was dripped onto a horizontally placed substrate from a microsyringe, and a still image was taken 1 second after the dripping with a video microscope to obtain the static contact angle of water. The measured values of the static contact angle of water were measured at 5 locations every 100 mm relative to the direction of travel, at the center and at a distance of 100 mm from each end. The average values are shown in Table 2. It should be noted that the contact values shown in Table 2 are initial values measured just after the film was manufactured.
[0185] (Static contact angle of n-hexadecane)
[0186] The static contact angle of n-hexadecane was measured using a fully automatic contact angle meter DropMaster700 (manufactured by Kyowa Interface Chemical Co., Ltd.) as follows. 2 μL of n-hexadecane was dripped onto a horizontally placed substrate from a microsyringe, and a still image was taken 1 second after the dripping with a video microscope to obtain the static contact angle. The measured values of the static contact angle of n-hexadecane were measured at 5 locations every 100 mm relative to the direction of travel, at the center and at a distance of 100 mm from each end. The average values are shown in Table 2. It should be noted that the contact values shown in Table 2 are initial values measured just after the film was manufactured.
[0187] (Bond strength with copper foil)
[0188] The film and electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) were used, and the copper foil, fluororesin film and copper foil were stacked in this order, and hot pressed using a vacuum hot press (model: MKP-1000HVWH-S7 / manufactured by Mikado Technos Co., Ltd.) at a pressing temperature of 320°C, a preheating time of 60 seconds, a pressure of 1.5 MPa, and a pressing time of 300 seconds. An aluminum plate was attached to one side of the laminate with an adhesive tape, and a 10 mm wide copper foil was grasped and stretched in a direction of 90° with respect to the plane of the laminate at a speed of 50 mm per minute using a Tensilon universal testing machine (manufactured by Shimadzu Corporation), thereby measuring the peel strength of the copper foil, and the obtained value was used as the bonding strength. The measured value is the average value of the measured values measured at 5 locations at intervals of 100 mm with respect to the traveling direction, at the center and at all three locations 100 mm from the left and right ends.
[0189] (Bond strength with prepreg)
[0190] As the prepreg material, prepreg R-5680 (J) (thickness 132 μm) (manufactured by Panasonic Corporation) was used, and the pressing conditions were set to a temperature of 200°C, a time of 75 minutes, and a pressure of 3.0 MPa. After the sample was prepared, the bonding strength was measured using the same method as the bonding strength with copper foil. The measured value is the average value of the measured values measured at 5 locations every 100 mm relative to the traveling direction at all three locations of the center and 100 mm from each end. The results are shown in Table 2.
[0191] (Adhesion strength between fluororesin films)
[0192] The surface treated surfaces of the fluororesin films were overlapped, and the samples made by hot pressing (200°C, 0.1MPa, 60s) were cut into strips with a width of 10mm. The unbonded parts of the strip samples were clamped with the upper and lower chucks of the Tensilon and stretched at a speed of 100mm per minute using a Tensilon universal testing machine (manufactured by Shimadzu Corporation). The peel strength was measured and the obtained value was used as the bonding strength. The measured value is the average value of the measured values measured at 5 locations at intervals of 100mm relative to the traveling direction at all 3 locations at 100mm from the center and the left and right ends. The results are shown in Table 2.
[0193] Regarding Examples 1 and 7, the dielectric constant and dielectric loss tangent were measured using a split cylinder resonator (10 GHz).
[0194] (Melting Point)
[0195] The temperature was raised at a rate of 10°C / min using a DSC apparatus and the result was calculated from the melting peak during measurement.
[0196] (Glass transition temperature)
[0197] The results are shown in Table 2. A solid dynamic viscoelasticity apparatus (DMA) was used to calculate tan δ from the peak during measurement at a frequency of 10 Hz, a strain of 0.1%, and a temperature increase rate of 5°C / min.
[0198] (Number of unstable functional groups)
[0199] The analysis was performed using FT-IR Spectrometer 1760X (manufactured by Perkin-Elmer).
[0200] (Thickness of fluororesin film)
[0201] The measurement was performed using a micrometer. It should be noted that, as shown in FIG1 , the thickness was measured at 12 locations every 5 mm in the width direction and every 20 cm in the traveling direction. The average of all the film thicknesses measured in this way is shown in the table as the "average film thickness of the surface". Furthermore, when the values are the same relative to the width direction, the average values of the 12 thicknesses measured in the traveling direction are calculated, and the difference between the maximum value and the average value is shown in the table.
[0202] (ESCA analysis of fluororesin film surface)
[0203] The measurement was performed using a scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA) PHI5000 VeraProbeII (manufactured by ULVAC-PHI Co., Ltd.) with the radiation source monochromatized to AlKα and the incident angle of 45°.
[0204] (Dielectric loss tangent)
[0205] The fluororesin film was used and the measurement was performed at 10 GHz (26° C.) using split cylinder resonators CR-710 and CR-740 (manufactured by EM labs), and the analysis was performed using a vector network analyzer P5007A (manufactured by Keysight Technologies).
[0206] (Rz)
[0207] The 200 μm diameter was measured using a color 3D laser microscope VK-9700 manufactured by KEYENCE. 2 Range of Rz.
[0208] [Table 2]
[0209]
[0210] As can be seen from the results in Table 2 above, the fluororesin film of the present disclosure has high uniformity in adhesive strength.
[0211] Industrial Applicability
[0212] The fluororesin film disclosed herein can be used for metal-clad laminates for circuit boards and the like.
Claims
1. A fluororesin film, which is a film composed of a composition containing a fluororesin, wherein: On at least one surface, at the center and at a position 100 mm away from the left and right ends, the average value of the contact angle with water measured at 5 locations every 100 mm relative to the traveling direction is less than 105°, and the average value of the contact angle with n-hexadecane measured at 5 locations every 100 mm relative to the traveling direction is less than 45°.
2. The fluororesin film according to claim 1, wherein The film width is 400 mm or more.
3. The fluororesin film according to claim 1 or 2, wherein The fluororesin includes tetrafluoroethylene-perfluoroalkylvinyl ether (PFA) and / or tetrafluoroethylene-hexafluoropropylene (FEP).
4. The fluororesin film according to any one of claims 1 to 3, wherein The dielectric loss tangent at 10GHz is less than 0.0015.
5. The fluororesin film according to any one of claims 1 to 4, wherein The dielectric loss tangent at 10GHz is less than 0.0010.
6. The fluororesin film according to any one of claims 1 to 5, wherein In every 1×10 6 The number of unstable functional groups in the main chain carbon atoms is less than 10.
7. The fluororesin film according to any one of claims 1 to 6, wherein The bonding strength between the metal foil having a surface roughness Rz of 1.5 μm or less and the fluororesin film at the center and at a position 100 mm away from the left and right ends is 0.8 N / mm or more.
8. The fluororesin film according to claims 1 to 7, wherein The bonding strength between the prepreg containing epoxy resin and / or polyphenylene ether and the fluororesin film at the center and at a position 50 mm away from each of the left and right ends is 0.8 N / mm or more.
9. The fluororesin film according to any one of claims 1 to 8, wherein When the films are bonded to each other on the same surface at 200° C., the adhesive strength is greater than 30 N / m on only one surface or both surfaces.
10. The fluororesin film according to claims 1 to 9, characterized in that The membrane is a long strip.
11. The fluororesin film according to any one of claims 1 to 10, which is used for a metal-clad laminate.
12. A metal-clad laminate comprising a metal foil and the fluororesin film according to any one of claims 1 to 11 as essential layers.
13. A metal-clad laminate, comprising a metal foil having a surface roughness Rz of 1.5 μm or less and a fluororesin film, wherein: The contact angle with water at the center and 100 mm from the left and right ends of the fluororesin film surface not facing the metal foil was 105° or less, and the contact angle with n-hexadecane was 45° or less.
14. The metal-clad laminate according to claim 13, wherein: The surface roughness Rz of the metal foil is 1.5 μm or less.
15. The metal-clad laminate according to claim 13 or 14, wherein: The bonding strength between the prepreg and the laminate at the center and at a position 100 mm away from each of the left and right ends was 0.8 N / mm or more.
16. The metal-clad laminate according to any one of claims 13 to 15, further comprising a layer other than the metal foil and the fluororesin film, The layer other than the metal foil and the fluororesin film is at least one selected from the group consisting of polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether and polybutadiene.
17. The metal-clad laminate according to any one of claims 13 to 16, wherein: The laminate is in the form of long strips.
18. The method for producing a metal-clad laminate according to claim 17, wherein: The method comprises the step of laminating a metal foil on the fluororesin film according to claim 10.
19. A circuit substrate, characterized in that: A metal-clad laminate according to any one of claims 13 to 16.
Citation Information
Patent Citations
Layered body and layered body production method
WO2020066457A1
Cited By
High-frequency flexible copper-clad plate and preparation method thereof
CN120792257A